Tổng hợp một số xeton alpha,beta-không no đi từ 3-axetyl-6-metoxi-4-metylcumarin. - Thảo, Nguyễn Minh; Thuấn, Nguyễn Văn; Nam, Trần Hoài; Thanh, Nguyễn Ngọc (Vietnam Journal of Chemistry, 2014)
By reaction of 2-hydroxy-5-methoxyacetophenone with ethyl acetoacetate has been prepared 3-acetyl-6-methoxy-4-methylcoumarin, which have condensed with aromatic aldehydes gave a,b-unsaturated ketones. Structure of these products was confirmed by IR, 1H-NMR and MS spectroscopic data.